2022
DOI: 10.1128/jvi.01233-22
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Protective Effect of Serial Infections with H5N8 Highly Pathogenic Avian Influenza Virus in Wild Ducks

Abstract: This study showed that ducks infected with a less-virulent HPAIV developed immunity that was protective against a subsequent infection with a more-virulent HPAIV 9 months later. Following 2014 H5N8 infection, the proportion of birds with detectable influenza nucleoprotein antibody declined from 100% (8/8) in tufted ducks and 78% (7/9) in mallards after 1 month to 33% (2/6) in tufted ducks and 29% (2/7) in mallards after 9 months.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 35 publications
2
21
0
Order By: Relevance
“…Comprehensive comparisons of both viral distribution and histopathological observations between experimentally and naturally infected white-tailed eagles imply that viral replication in the brain is responsible for the disease severity and mortality in this species. Caliendo et al (2022) inoculated two species of wild ducks-tufted duck (Aythya fuligula) and mallard (Anas platyrhynchos)-first with 2014 H5N8 HPAI virus and after 9 months with 2016 H5N8 HPAI virus, to test the hypothesis that previous infection with a HPAI virus provides long-term immunity against subsequent infection with another HPAI virus. Both viruses belong to the 2.3.4.4b clade.…”
Section: Hpai In Wild Birdsmentioning
confidence: 99%
“…Comprehensive comparisons of both viral distribution and histopathological observations between experimentally and naturally infected white-tailed eagles imply that viral replication in the brain is responsible for the disease severity and mortality in this species. Caliendo et al (2022) inoculated two species of wild ducks-tufted duck (Aythya fuligula) and mallard (Anas platyrhynchos)-first with 2014 H5N8 HPAI virus and after 9 months with 2016 H5N8 HPAI virus, to test the hypothesis that previous infection with a HPAI virus provides long-term immunity against subsequent infection with another HPAI virus. Both viruses belong to the 2.3.4.4b clade.…”
Section: Hpai In Wild Birdsmentioning
confidence: 99%
“…H5 AIV spread to other regions through bird migration 45 and the poultry trade 46 , and our results reveal a 2-3- year delay between the peak of lineage dissemination from Chinese poultry and the peak of lineage introduction into European poultry. Although it has been suggested that the intercontinental spread of H5 AIV may occur within a single avian migratory cycle 8,45, 4750 , the delay we observe may be attributed in part to pre-existing immunity in wild birds, which may provide partial protection against infection and disease 5153 , leading to reduced circulation and potentially dampening large-scale outbreaks in wild birds. However, the duration of protection conferred by previous AIV infection and its impact on the epidemiology of AIV have yet to be elucidated fully 54 .…”
Section: Discussionmentioning
confidence: 63%
“…Wade, Ashton-Butt, Scott et al suggest other measurements to detect and count infected wild birds such as utilisation and expansion of hunter harvested AI surveillance network [ 19 ]. Furthermore, some wild bird species may have developed antibodies overtime which could have influenced the observed and recorded numbers in some areas [ 20 ].…”
Section: Discussionmentioning
confidence: 99%